Urban furniture selection. - Broto, Carles; Krauel, Jacobo; Morales, Marianna (Barcelona : Linksbooks, 2009)
Hundreds of benches, rails, parterres, street lamps, posts, footpaths and bridges, fountains and spatial organizers... This exhaustive volume contains all of the elements that go into the design of urban space. All elements in this volume were customdesigned for specific urban projects and all of them are explained from the drawing board up: from the original sketches and lists of materials, to the finished product in its setting. This is the most thorough volume of its kind available and contains material that all urban design professionals must be familiar with.
boek